Mediator Non-Hakim di Aceh: Menelisik Peran Peradilan Adat Dalam Penyelesaian Kasus Sengketa - Nisa, Khairun; Azwir, Azwir; Muhazir, Muhazir (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
The customary courts in Aceh have long served as a traditional mechanism for dispute resolution, prioritizing deliberation and consensus. Although formal recognition through Aceh Qanun No. 9 of 2008 has strengthened the role of customary institutions in maintaining social order and resolving disputes quickly and simply, its implementation still faces challenges that affect its consistency and effectiveness. This study aims to analyze the role of customary courts as an effective instrument for dispute resolution, identify the challenges encountered, and contribute to developing dispute resolution mechanisms based on customary practices in Aceh. The research employs a qualitative method with a descriptive approach. Data were obtained through interviews with the Deputy Chair of the Aceh Customary Assembly of Langsa City and an analysis of official documents, such as customary mediation records. Based on the data, out of 82 cases handled between 2021 and 2023, 73 were successfully resolved through customary mediation, including family disputes and interpersonal conflicts. These findings highlight the significant role of customary courts in fostering peaceful solutions accepted by the community. The main challenges identified include insufficient administrative support, inadequate documentation, and differing procedural understandings among customary leaders. This study contributes by offering strategic recommendations, such as strengthening the capacity of customary leaders through training, developing documentation systems, and enhancing coordination with law enforcement agencies. These efforts aim to ensure that customary courts continue to evolve as an effective, sustainable, and relevant mechanism for dispute resolution within the national legal system.